Revisiting Old Ionophore Lasalocid as a Novel Inhibitor of Multiple Toxins - Mahtal, Nassim (Toxins (Basel), 2020)
The ionophore lasalocid is widely used as a veterinary drug against coccidiosis. We found recently that lasalocid protects cells from two unrelated bacterial toxins, the cytotoxic necrotizing factor-1 (CNF1) from Escherichia. coli and diphtheria toxin. We evaluated lasalocid’s capacity to protect cells against other toxins of medical interest comprising toxin B from Clostridium difficile, Shiga-like toxin 1 from enterohemorrhagic E. coli and exotoxin A from Pseudomonas aeruginosa. We further characterized the impact of lasalocid on the endolysosomal and the retrograde pathways and organelle integrity, especially the Golgi apparatus. We found that lasalocid protects cells from all toxins tested and impairs the drop of vesicular pH along the trafficking pathways that are required for toxin sorting and translocation to the cytoplasm. Lasalocid also has an impact on the cellular distribution of GOLPH4 and GOLPH2 Golgi markers. Other intracellular trafficking compartments positive for EEA1 and Rab9A display a modified cellular pattern. In conclusion, lasalocid protects cells from multiple deadly bacterial toxins by corrupting vesicular trafficking and Golgi stack homeostasis.